PERANAN IBU RUMAH TANGGA DALAM USAHA MENINGKATKAN PENDAPATAN KELUARGA PADA KERAJINAN TEDUNG DI DESA PAKSEBALI KEC. DAWAN KAB. KLUNGKUNG - Susanti, Ni Ketut; Agung, Anak Agung Putu; Legawa, I Made (Universitas Mahasaarswati Denpasar, 2012)
The purpose of the research to find out the role of housewife cobra craft in order to increase family income and determine the factors that affect it. Sample in this study is pengerajin fiery housewife of 40 people. Data obtained by interview using kuisioner and further analyzed with multiple linear regression test.The results showed a strong relationship between the availability of skills variables, age, level of formal education, an endless hours of work and motivation to increase family income indicated by the double correlation (R) of 0.862. Simultaneous influence of family income female workers craft cobra explained by age, level of formal education, skills, flushing hours of work and motivation is 74.20%, while the remaining 25.80% is influenced by other factors.Viewed from the contribution income crafting fiery housewife on total family income per month figures obtained 1,278,750 (38.50%) from 3,321,250 to the lowest range is 1050000 (37.50% and the highest is 1500 .000, - (38.46%). Given the very large role of housewife in the family expected to increase the revenue the government cant provide contruction and counseling so that they can produce more quality productions.